2022
DOI: 10.56341/amj.v3i1.121
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Accountability and Transparency In The Allocation of School Operational Assistance Funds (BOS) During Covid-19.

Abstract: UPT SD Negeri 191 Bubun Bia is one of the public schools that also received attention in the form of BOS funds from the government. The purpose of this study was to find out how to apply the principles of transparency and accountability in the management of BOS funds during the COVID-19 pandemic at UPT SD Negeri 191 Bubun Bia. This study uses qualitative methods with descriptive analysis and data collection techniques by means of observation, interviews, and documentation.  The distribution of BOS Funds is bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Furthermore, there is research conducted by (Lesmana et al, 2022) with the results of the study showing that religiosity has a significant and partial effect on interest. Accountability is the legal and moral obligation of individuals, companies, or organizations to clarify the use of equipment, money, or authority handed over by third parties as a responsibility to interest owners and beneficiaries (Nurul et al, 2022). BAZNAS is a zakat management institution that is closely related to religiosity.…”
Section: The Effect Of Religiosity As Moderation In the Effect Of Acc...mentioning
confidence: 99%
“…Furthermore, there is research conducted by (Lesmana et al, 2022) with the results of the study showing that religiosity has a significant and partial effect on interest. Accountability is the legal and moral obligation of individuals, companies, or organizations to clarify the use of equipment, money, or authority handed over by third parties as a responsibility to interest owners and beneficiaries (Nurul et al, 2022). BAZNAS is a zakat management institution that is closely related to religiosity.…”
Section: The Effect Of Religiosity As Moderation In the Effect Of Acc...mentioning
confidence: 99%
“…The dropout rate in elementary schools in Indonesia was still high. However, the government had launched the government funding program named Bantuan Operasional Sekolah (BOS) or School Operational Assitance (Aniza, 2023;Bandur et al, 2022;Fatima et al, 2022;Purwaningsih & Dardjito, 2021;Romlah et al, 2023;Sutanto et al, 2021). Some previous studies identified the factors influencing dropout.…”
Section: Introductionmentioning
confidence: 99%
“…The dropout rate in elementary schools in Indonesia was still high. However, the government had launched the government funding program named Bantuan Operasional Sekolah (BOS) or School Operational Assitance(Aniza, 2023;Bandur et al, 2022;Fatima et al, 2022;Purwaningsih & Dardjito, 2021;Romlah et al, 2023;Sutanto et al, 2021). Some previous studies identified the factors influencing dropout.Rumberger & Lim (2018) identified two types of factors that predict whether students drop out or graduate from high school: factors associated with the individual characteristics of students and factors associated with the institutional characteristics of their families, schools, and communities.…”
mentioning
confidence: 99%